INTEGRITY OF THE PEDAGOGICAL PROCESS IN SCHOOLS WITH INCLUSIVE FORM OF EDUCATION - Nadiya Ashytok ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article analyses the approaches to the definition of "integrity". There were considered such pedagogical aspects of integrity as the integrity of the goals and the contents of education, the integrity of system of teaching methods. It is shown that the idea of integrity is a backbone one for developing the educational programs or lessons. The article substantiates the need for appropriate teaching aids for the integrity of the pedagogical process, which would promote the consistency of its components - purpose, educational information, schoolchildren, teachers, methods, forms, teaching aids. The article examines the methodological regulators of building a modern strategy of a holistic approach to the study and design of educational reality.